THE USE OF VIDEO AS A MEDIA TO IMPROVE THE SPEAKING SKILL OF THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL - Pijar Ganda Subrata; TMA. Kristanto (Universitas Sarjanawiyata Tamansiswa, 2019)
The research focused on teaching speaking using audio visual media. The objectives of the study are how to implement audio visual media to improve students’ speaking skill and to describe the effectiveness of using audio visual media in the teaching of speaking. This study used a classroom action research design. The researcher and the collaborator worked together in designing the lesson plan, setting the criteria of success, implementing the action, observing the action, and having reflection. The subjects of this study were twenty eight students of the eleventh grade students of SMA N 1 Ngaglik, Sleman in academic year 2017/2018. This study was conducted in two cycles by following the procedures of the action research i.e. planning, implementing, observing, and reflecting. The activities of each cycle were Pre-speaking activities, While-speaking Activities, and Post-speaking activities. The result of the study showed that the use of audio visual media were able to improve the students' speaking skills. The percentage of the students achieving the score above predetermined minimum passing grade (KKM) had improved from 7.15% (2 of 28 students) in the preliminary study to 64.2% (18 of 28 students) in Cycle 1, and to 96.4% (27 28 students) in Cycle 2. Besides, the mean scores of each aspect of fluency, grammar, pronunciation, vocabulary, confidence were also increased.